Mechanism understanding for stripping electrochemistry of Li metal anode - Jiang, Feng‐Ni; Yang, Shi‐Jie; Liu, He; Cheng, Xin‐Bing; Liu, Lei; Xiang, Rong; Zhang, Qiang; Kaskel, Stefan; Huang, Jia‐Qi (SusMat (Online), 2021)
Lithium metal batteries with theoretically high energy density are strongly considered as a potential electrochemical storage system. Dead lithium formed in the stripping process of lithium metal anode significantly hinders the practical applications. This review comprehensively summarizes the current research status about the stripping electrochemistry of lithium metal anode. The stripping models in different electrochemical scenarios are discussed. The factors affecting stripping processes and corresponding solutions are outlined. This review affords fresh insights to design robust lithium metal batteries based on the comprehensive understanding of the stripping electrochemistry. (DOI: https://doi.org/10.1002/sus2.37)